155 Lycium Barbarum Polysaccharides Improves Erectile Function Through Suppression of Inflammation and Apoptosis in Rats with Bilateral Cavernous Nerve Injury. (1st May 2022) - Wang, J.; Song, J.; Song, G.; Hu, P.; Sun, T.; Liu, K.; Xu, W.; Liu, J.; Ruan, Y.
ABSTRACT: Introduction: Neurogenic erectile dysfunction (NED) responds poorly to phosphodiesterase 5 (PDE5) inhibitors. Lycium barbarum polysaccharide (LBP) has broad-spectrum anti-inflammatory and anti-apoptotic effects, but whether it improves the erectile function of neuropathic ED through the above-mentioned mechanism is unclear. Objective: We intend to explore the role of LBP in the treatment of NED. Methods: A rat model of bilateral cavernous nerve injury (BCNI) was constructed by crushing the CN 5 mm distal to the major pelvic ganglion (MPG). Tweety-four BCNI rats were randomly divided into BCNI group, BCNI + LBP-LD (20 mg/kg/day) group and BCNI + LBP-HD (40 mg/kg/day) group, whereas another 8 age-matched rats formed the control group. Erectile function was evaluated by measuring intracavernosal pressure (ICP) and mean arterial pressure (MAP). The penile tissues, and MPG along with CN were collected from each group of rats for subsequent histological and molecular biological analysis. The rat Schwann cell line S16 was used for CCK-8 and wound healing assay, and the Schwann cell (SC) markers S100 and Pmp22, neuroinflammatory indicators IL-1β, TGF-β1, apoptosis-related proteins Caspase-3, Bax, Bcl-2 and nerve growth factor NGF were verified by PCR and WB. Results: ICP/MAP indicated that the erectile function of rats in the BCNI model group was severely impaired, which was rescued in the BCNI+LBP-LD and BCNI+LBP-HD groups. Rats in the BCNI model group can highly express inflammatory indicators NF-kb, TNF-α and apoptosis-related proteins Bax, Caspase-3. TUNEL confirmed that the level of apoptosis in the penile tissue of BCNI rats increased. The above-mentioned penile inflammation and apoptosis changes can be inhibited by LBP. In addition, both immunofluorescence and WB confirmed that rats in the LBP-LD and LBP-HD groups highly expressed nNOS and down-regulated the expression of TH. In vitro experiments have shown that LBP can promote the proliferation and migration of SC, increase the expression of Pmp22 and NGF, and the inflammation and apoptosis-related proteins were down-regulated. Conclusion: LBP can relieve the inflammation and apoptosis at the original site of nerve injury by promoting the proliferation and migration of SC, and secretion of NGF, thereby inhibiting the inflammation and apoptosis caused by hypoxia after denervation of penile tissue, and improving penile erection. Disclosure: Work supported by industry: no.